KERANGKA BERPIKIR WALI SONGO DAN ISLAMISASI JAWA PADA PERALIHAN ABAD XV DAN XVI - Adib, Muhammad (LP3M IAI Al-Qolam, 2023)
This research aims to explore the framework of thought used by the Wali Songo in the process of massive Islamization in Java during the transition period of the 15th and 16th centuries. A historical-philosophical approach is used to explore the thoughts and da'wah strategies carried out by Wali Songo in dealing with the social conditions of Javanese society at that time. The content analysis method is used to analyze historical texts and related literature which contain the preaching activities of the Wali Songo. The research results show that the Wali Songo's frame of mind is reflected through the social analysis and da'wah strategies they use. Through a deep understanding of local communities and their spiritual needs, the Wali Songo use an approach appropriate to the Javanese cultural context to spread Islamic teachings on a massive scale. They adopted an inclusive and adaptive da'wah method, utilizing local culture, language and traditions to form an understanding of Islam that was relevant and acceptable to Javanese society at that time. This research contributes to an understanding of the dynamics of Islamization in Java during that period, as well as the relevance of the da'wah strategies used by the Wali Songo in different social and cultural contexts.